"This Group is Like a Home to Me:" understandings of health of LGBTQ refugees in a Swedish health-related integration intervention: a qualitative study - Pelle Pelters; Krister Hertting; Catrine Kostenius; Eva-Carin Lindgren (BMC, 2022)
Abstract Background When large numbers of asylum seekers immigrate to a country, civil society is encouraged to contribute to their integration. A subgroup of asylum seekers comprising lesbian, gay, bisexual, transgender, or queer (LGBTQ) refugees are specifically deemed vulnerable to developing health and integration problems due to the double stigma of being a sexual/gender minority and a refugee. The Swedish Federation for LGBTQ Rights (RFSL) is a civil societal organization that has established the support group "RFSL Newcomers," a health-related integration intervention that targets such refugees. The aim of the present study is reconstructing the subjective understanding of health of LGBTQ refugees. Methods Eleven participants in Newcomers and eight organizers were interviewed about LGBTQ refugees' experiences of migrating and participating in RFSL Newcomers. Qualitative content analysis was used to reconstruct subjective understandings of health that were constructed in these narratives. As the data did not originally concentrate on exploring understandings of health, a broad theoretical approach was used as a heuristic for the analysis, which focused on the common everyday approach of conceptualizing health as wellbeing. Results The narratives revealed three interconnected, interdependent categories of understanding health in which tensions occur between wellbeing and ill-being: belonging versus alienation, security and safety versus insecurity, and recognition versus denial. The categories contribute to an overarching theme of health as framed freedom - i.e., freedom framed by conditions of society. Conclusions For our participants, belonging, recognition, and security/safety are conceptual elements of understanding health, not its social determinants. Thus, these understandings emphasize relational and existential meanings of health (theoretical implication). As for practical implications, the understandings of health were connected to being either inside or outside the Newcomers group and a new society, depending on whether LGBTQ refugees comply with social requirements. As a significant actor that is representative of the cultural majority and a facilitator of LGBTQ refugees' resettlement process, RFSL provides LGBTQ refugees with crucial orientations for becoming a "good migrant" and a "good LGBTQ person," yet a "bad bio-citizen." Generally, organizers of interventions may enhance the effectiveness of their interventions when relational, existential, and biomedical understandings of health are all incorporated.